1995
DOI: 10.1128/aac.39.11.2426
|View full text |Cite
|
Sign up to set email alerts
|

T30177, an oligonucleotide stabilized by an intramolecular guanosine octet, is a potent inhibitor of laboratory strains and clinical isolates of human immunodeficiency virus type 1

Abstract: T30177, an oligonucleotide composed of only deoxyguanosine and thymidine, is 17 nucleotides in length and contains single phosphorothioate internucleoside linkages at its 5 and 3 ends for stability. This oligonucleotide does not share significant primary sequence homology with or possess any complementary (antisense) sequence motifs to the human immunodeficiency virus type 1 (HIV-1) genome. T30177 inhibited replication of multiple laboratory strains of HIV-1 in human T-cell lines, peripheral blood lymphocytes,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
112
1
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 40 publications
0
112
1
1
Order By: Relevance
“…This effectiveness was contradictory to the previous determination that well-known adsorption and fusion inhibitors such as dextran sulphate and soluble CD4 are more effective against laboratory strains than primary clinical isolates (Daar et al, 1990;Meylan et al, '1994), but seemed to agree with the results published by Ojwang et al (1995). Wyatt et al (1994) reported that the hyperstructure of a short G-rich ODN with a phophorothioate backbone was essential for preventing cell-to-cell infection and acute infection.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…This effectiveness was contradictory to the previous determination that well-known adsorption and fusion inhibitors such as dextran sulphate and soluble CD4 are more effective against laboratory strains than primary clinical isolates (Daar et al, 1990;Meylan et al, '1994), but seemed to agree with the results published by Ojwang et al (1995). Wyatt et al (1994) reported that the hyperstructure of a short G-rich ODN with a phophorothioate backbone was essential for preventing cell-to-cell infection and acute infection.…”
Section: Discussioncontrasting
confidence: 56%
“…For example, ISIS5320, consisting of an 8-mer G-rich sequence (5' TTGGGGTT 3') with a phosphorothioate backbone, which is folded into an intramolecular G-tetrad, exerts anti-HIV activity by preventing the binding of the V3 loop of HIV to CD4 (Wyatt et al, 1994). Furthermore, T30177, an ODN composed entirely of deoxyguanosine and thymidine modified with a single phosphorothioate internucleoside linkage at its 5' and 3' ends, inhibits replication of both laboratory strains and clinical isolates by inhibiting HIV-1 integrase activity and/or by blocking the interaction between gp120 and CD4 (Ojwang et al, 1994(Ojwang et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%
“…T30177 is a 17-mer ODN that comprises only deoxyguanosine and thymidine residues stabilized by an intramolecular guanosine octet. 20 T30177 contains single phosphorothioate internucleoside linkages at its 5' and 3' ends, and has shown strong anti-HIV activity in infected cells on the basis of its 3-dimensional structure.…”
Section: Antisense and Control Odnsmentioning
confidence: 99%
“…For most of the IN inhibitors that did show antiviral activity in cell culture, it was not unambiguously demonstrated that the integration step was targeted. Moreover, for two classes of IN inhibitors with antiviral activity, the G quartets (24) and L-chicoric acid derivatives (32), it has been demonstrated by means of selecting and sequencing drug-resistant HIV-1 strains that viral entry and not integration is the main antiviral target in cell culture (13,27). In contrast, Ojwang et al (24) reported that G quartets generated an increase in two-LTR circles and a decrease in integrated DNA at concentrations that inhibit viral replication.…”
mentioning
confidence: 99%